Home Alone: Elimination of All but One Alternative Sigma Factor in Listeria monocytogenes Allows Prediction of New Roles for σB - Liu, Yichang; Orsi, Renato H.; Boor, Kathryn J.; Wiedmann, Martin; Guariglia-Oropeza, Veronica (Frontiers in Microbiology, 2017)
Among Listeria monocytogenes’ four alternative σ factors, σB controls the largest regulon. As σB-dependent transcription of some genes may be masked by overlaps among regulons, and as some σB-dependent genes are expressed only under very specific conditions, we hypothesized that the σB regulon is not yet fully defined. To further extend our understanding of the σB regulon, we used RNA-seq to identify σB-dependent genes in an L. monocytogenes strain that expresses σB following rhamnose induction, and in which genes encoding the other alternative sigma factors have been deleted. Analysis of RNA-seq data with multiple bioinformatics approaches, including a sliding window method that detects differentially transcribed 5’ untranslated regions (UTRs), identified 105 σB-dependent transcription units (TUs) comprising 201 genes preceded by σB-dependent promoters. Of these 105 TUs, 7 TUs comprising 15 genes had not been identified previously as σB-dependent. An additional 23 genes not reported previously as σB-dependent were identified in 9 previously recognized σB-dependent TUs. Overall, 38 of these 201 genes had not been identified previously as members of the L. monocytogenes σB regulon. These newly identified σB-dependent genes encode proteins annotated as being involved in transcriptional regulation, oxidative and osmotic stress response, and in metabolism of energy, carbon and nucleotides. In total, eighteen putative σB-dependent promoters were newly identified. Interestingly, a number of genes previously identified as σB-dependent did not show significant evidence for σB-dependent transcription in our experiments. Based on promoter analyses, a number of these genes showed evidence for co-regulation by σB and other transcriptional factors, suggesting that some σB-dependent genes require additional transcriptional regulators along with σB for transcription. Over-expression of a single alternative sigma factor in the absence of all other alternative sigma factors allowed us to: (i) identify new σB-dependent functions in L. monocytogenes, such as regulation of genes involved in 1,2-propanediol utilization (LMRG_00594-LMRG_00611) and biosynthesis of pyrimidine nucleotides (LMRG_00978-LMRG_00985); and (ii) identify new σB-dependent genes involved in stress response and pathogenesis functions. These data further support that σB not only regulates stress response functions, but also plays a broad role in L. monocytogenes homeostasis and resilience.